Developing fluency and comprehension with the secondary fluency routine. Issue 3 (30th March 2021) - Landreth, Shelly J.; Young, Chase
Abstract: This article examines the effects of a reading fluency intervention on the fluency and comprehension of struggling middle school readers. The secondary fluency routine was developed by the first author, and was based on effective practices described in other studies. Thirty-nine seventh and eighth grade students enrolled in reading intervention classes participated in the study, which lasted for a period of 18 weeks. Students in the treatment classes participated in the Secondary Fluency Routine for 10 minutes daily, while students in the comparison classrooms participated in independent reading during that time. Participants were pre- and posttested using the GORT-5. A repeated measures analysis of variance was conducted on all outcome measures which included rate, accuracy, fluency, oral reading index, prosody, and comprehension. There were no interaction effects; however, main effects were detected on all measures, and mean difference effect sizes indicated that the intervention was effective in increasing reading fluency and comprehension.